Comparisons of Alcohol and Drug Dependence in Terms of Attachments and Clinical Issues. (2nd January 2018) - Zeid, Dana; Carter, Joshua; Lindberg, Marc A.
ABSTRACT: Background : Alcohol and drug dependencies are associated with different social stigmas, and some studies suggest they might exhibit different clinical presentations. Further, the treatments for each vary considerably. Alcohol versus drug use problems were compared in terms of attachment patterns and related clinical treatment issues in two interlocking studies using converging logic and designs. Methods : In Study 1, alcohol versus drug dependence was defined in terms of a known groups design. Patients from an inpatient alcohol treatment center, patients receiving treatment for opiate dependence in a methadone maintenance clinic, and controls were compared on the 29 scales of the Attachment and Clinical Issues Questionnaire (ACIQ). Study 2 sampled a substantially different population (491 university students) and used different operational definitions of substance use problems, relying on screening instruments. Results : Study 1 found that, although the drug and alcohol dependent patients differed substantially from the controls, they did not differ from one another on any of the 29 ACIQ scales measuring attachments and clinical issues. Study 2 converged on the known groups design of Study 1, showing convergent and concurrent rather than discriminate evidence for the alcohol and drug dependence screening instruments. Conclusion : Alcohol and drug dependencies were not found to differ significantly in terms of attachments or clinical issues. These studies aimed to provide clearer and more empirically grounded guidance to the clinician and researcher.